2021
DOI: 10.3389/fpsyt.2021.645340
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Medical Students About Their Role and Social Accountability in the COVID-19 Pandemic

Abstract: Background: In this study, we aimed to explore the attitude of medical students toward their role and social accountability in this pandemic era. An online survey was developed to elicit information on (1) the role of medical students in the pandemic era; (2) Medical education in the “new normal,” and (3) the impact of COVID-19 on medical students.Methods: The online survey, developed by a team consisting of three medical students, three psychiatry residents, and three professors of psychiatry, was conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
5
13
0
Order By: Relevance
“…In our study, students reported that they were quite ready to fight the pandemic. This appears consistent with other studies in other national contexts, in which students indicated their willingness to join the healthcare response to the COVID-19 pandemic ( Hong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, students reported that they were quite ready to fight the pandemic. This appears consistent with other studies in other national contexts, in which students indicated their willingness to join the healthcare response to the COVID-19 pandemic ( Hong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although virtual classes were introduced as a part of social distancing, due to the nature of medical education, medical students were scheduled to meet for on-site education in venues like laboratory classes in basic medicine, clinical clerkship in training hospitals, and medical licensing examinations ( 4 ). Medical students are on the cusp of becoming medical experts as they are not yet certified medical professionals but are still trainees in the field ( 5 ). They may feel the responsibility of being medical experts, in spite of inadequate medical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the threats and demands of the COVID pandemic, for example, many health professionals have reported diminished sleep and increased stress, anxiety, and burnout ( 1 14 ), and similar negative effects have been seen in health professions students ( 15 20 ). These effects may limit the time and physical or mental resources available to regularly engage in new behaviors (e.g., start an exercise routine, meditate, go to bed earlier) that could help promote well-being and resilience.…”
Section: Discussionmentioning
confidence: 98%
“…The result for many has been diminished sleep and increased stress, anxiety, and burnout ( 1 14 ). Due to COVID-19-related restrictions, the requisite shifts from in-person to online learning, and the resulting decrease in social support and interaction, similar negative effects have been seen in health professions students ( 15 20 ). In addition to the negative impact of these stressors on health professionals, there are negative implications for patient safety as well ( 21 ).…”
Section: Introductionmentioning
confidence: 91%